15. Isolation of Pseudomonas sp . That failed to hatch quail’s eggs (coturnix-coturnix japonica ) in Garot, Darul Imarah Subdistric, Aceh Besar - Dara Hayati Rapi; Erina Erina; Darniati Darniati (Jurnal Medika Veterinaria, 2017)
The research aimed to isolate Pseudomonas sp from fail to hatch quail eggs in Garot village, Darul Imarah subdistrict, Aceh Besar. Thirty failed to hatch quail eggs were examined in microbiology laboratory of Veternery Medical, Faculty Syiah Kuala University. Modification of examined Carter method was used in this research. The result of this research showed 12 of 30 samples examine we were positive infected by pseudomonas sp. It can concluded that bacteria Pseudomonas sp is one of the causes of failure hatching quail eggs in Garot village, Darul Imarah subdistrict, Aceh Besar